Digital Innovation in Education: The Impact of Problem-Based Learning Enhanced by Google Sites on Students' Critical Thinking in Seismic Studies - Rahmalia Kurnia Wardani; Purwanto; Djoko Soelistijo; Adelina Tang; Muhammad Mu’tashimbillah (Future Space: Studies in Geo-Education, 2024)
Problem-Based Learning (PBL) is an effective model for developing students' critical thinking skills in addressing geosphere-related problems. The application of the PBL model provide interactive educational content that supports analysis and problem solving on seismic materials.  This study examines the impact of integrating Google Sites into PBL on students' critical thinking, with a focus on seismic phenomena, a critical topic in geography education. The research was carried out in Madrasah Aliyah Negeri (MAN) 1 Malang using the post-test control group design design with experimental class X.C and control class X.E. Critical thinking tests have been tested for validity and reliability using critical thinking indicators adapted from Irmawati. Independent sample t-test results with Sig. (2- tailed) are 0,000 or < 0.05 and the ratio of critical thought skills in experimental classes is higher than in control class. The findings indicate a statistically significant improvement in critical thinking skills for students in the experimental group (PBL with Google Sites) compared to the control group (conventional methods). The integration of the PBL model with Google Sites promotes ongoing student collaboration and enhances critical thinking skills in analyzing real-world seismic issues.